Data from: Many places called home: the adaptive value of seasonal adjustments in range fidelity - Lafontaine, Alexandre; Drapeau, Pierre; Fortin, Daniel; St-Laurent, Martin-Hugues (Zenodo, 2018)
1. The vast majority of animal species display range fidelity, a space-use behaviour enhancing familiarity with local habitat features. While the fitness benefits of this behaviour have been demonstrated in a variety of taxa, some species or populations rather display infidelity, displacing their home range over time. Others, such as many ungulate species, show seasonal adjustments in their range fidelity to accommodate changes in the dominance of limiting factors or in the distribution of resources. 2. Few empirical studies have explored the adaptive value of seasonal adjustments in range fidelity. Using boreal populations of woodland caribou (Rangifer tarandus caribou) as a biological model, we evaluated how range fidelity impacted individual performance during two seasons where juvenile and adult survival are limited by different predation pressures. 3. Between 2004 and 2013, we monitored the survival, reproductive success, habitat selection and range fidelity of female caribou in the boreal forest of eastern Canada. Using resource selection functions, we assessed how seasonal range fidelity was linked to two fitness correlates: calf survival in summer and adult female survival in winter. 4. Females displayed season-specific space use tactics: they selected previously used areas during calving and summer, but tended to shift their winter range from one year to the next. During calving and summer, range fidelity yielded relatively high fitness benefits, as females that did not lose their calf displayed stronger fidelity than females that did. In winter, however, adult survival was negatively linked to range fidelity, as females that survived selected areas further away from their seasonal range of the previous year than females that died. 5. We provide one of the first evidences that making seasonal adjustments in range fidelity can be an adaptive behaviour influencing the spatial distribution of a threatened species. Assessing the seasonal nature of range fidelity tactics may improve our predictions of space ...